Aggression and violence in sport
The use of the word "aggression" is somewhat confusing. The term aggression is employed to describe angry violent behavior with intent to hurt a person or cause damage to property. "Aggressive" behavior is also used to depict a strong and somewhat adventurous effort. Thus an aggressive sales person or athlete, for example, may be perceived as obnoxious or violent by some and motivated and hard working by others. Baron (1977, p. 12, cited in Cox, 1990, p. 266) offers the following definition for aggression: "Aggression is any form of behavior directed toward the goal of harming or injuring another living being who is motivated to avoid such treatment." Thus: Aggression is an act not a cognitive state Aggression is not accidental, it is an intentional act to harm. Aggressive acts involve both bodily and psychological harm. Aggressive acts involve only living beings; harm to objects does not count as aggression. The receiver of aggression does not want to get hurt. Bredemeier (1983) defined aggressive behavior in sport as: "The intentional initiation of violent and or injurious behavior. 'Violent' means any physical, verbal or nonverbal offense, while 'injurious behaviors' stand for any harmful intentions or actions." Thus: An accidental foul or injury inflicted on another athlete resulting from inferior skills, will not be considered as aggression. An intentional foul, although not resulting in any harm or injury, is considered as sport aggression. Bredemeier's (1983) definition isn't clear about (a) whether harm to objects counts as aggression or (b) whether acts performed in a sadistic--masochistic relationship may be viewed as aggressive...